Do toxicokinetic and toxicodynamic processes hold the same for light and heavy rare earth elements in terrestrial organism Enchytraeus crypticus?. (July 2020) - Huang, Xueying; He, Erkai; Qiu, Hao; Zhang, Lulu; Tang, Yetao; Zhao, Chunmei; Li, Min; Xiao, Xue; Qiu, Rongliang
Abstract: The widespread use of rare earth elements (REEs) in numerous sectors have resulted in their release into the environment. Existing knowledge about the effects of REEs were acquired mainly based on toxicity tests with aquatic organisms and a fixed exposure time, Here, the dynamic accumulation and toxicity of REEs (La, Ce, and Gd) in soil organism Enchytraeus crypticus were determined and modeled by a first-order one-compartment model and a time-toxicity logistic model, respectively. Generally, the accumulation and toxicity of REEs were both exposure level- and time-dependent. The overall uptake rate constants were 2.97, 2.48, and 2.38 L kg −1 d −1 for La, Ce, and Gd, respectively. The corresponding elimination rate constants were 0.99, 0.78, and 0.56 d −1, respectively. The worms exhibited faster uptake and elimination ability for light REEs (La and Ce) than for heavy REEs (Gd). For all three REEs, the LC50 values based on exposure concentrations decreased with time and reached ultimate values after approximately 10 d exposure. The estimated ultimate LC50 values (LC50∞) were 279, 334, and 358 mg L −1 for Ce, Gd, and La, respectively. When expressed as body concentration, the LC50inter value was almost constant with time, demonstrating that internal body concentration could be a better indicator of dynamic toxicity of REEs than external dose. This study highlights that specific REE and exposure time should be taken into account in accurately assessing risk of REEs. Graphical abstract: Image 100426 Highlights: Toxicokinetics and toxicodynamics of REEs in E. crypticus were investigated. E. crypticus had higher uptake and elimination ability for La and Ce than for Gd. Ce showed to be most toxic element even Gd was mostly accumulated in E. crypticus . Internal dose of REE correlated better with dynamic toxic effect than external dose. Abstract : Toxicokinetics and toxicodynamics of REEs should be incorporated in assessing their risks to soil organism.